ELECTRON-SPIN POLARIZATION IN PHOTOSYNTHETIC BACTERIA - ANISOTROPIC CHEMICAL-REACTIVITY - Hore, P; Hunter, D; Riley, D; Semlyen, J; Vanwijk, F; Schaafsma, T; Gast, P; Hoff, A (1991)
It is shown that electron spin polarization can be used to probe the anisotropy of singlet-triplet interconversion of radical pairs involved in photosynthetic charge separation. Anisotropic polarization may be observed with non-oriented reaction centres, provided an anisotropic interaction (e.g. zero-field splitting or g-tensor anisotropy) produces resolvable structure in the EPR spectrum of the reaction intermediates. Two examples, both for prereduced bacterial reaction centres, are discussed: (i) the triplet state of the primary donor (a bactenochlorophyll dimer) and (ii) the reduced secondary acceptor (a semiquinone). Computer simulations are used to understand the observed behaviour and yield information on the magnetic and electronic interactions involved in electron transport. © 1991 Springer.